CD151 Accelerates Breast Cancer by Regulating α(6) Integrin Function, Signaling, and Molecular Organization - Yang, Xiuwei H. (Cancer Res, 2008)
CD151, a master regulator of laminin-binding integrins (α(6)β(4), α(6)β(1), and α(3)β(1)), assembles these integrins into complexes called tetraspanin-enriched microdomains. CD151 protein expression is elevated in 31% of human breast cancers and is even more elevated in high-grade (40%) and estrogen receptor–negative (45%) subtypes. The latter includes triple-negative (estrogen receptor, progesterone receptor, and HER2 negative) basal-like tumors. CD151 ablation markedly reduced basal-like mammary cell migration, invasion, spreading, and signaling (through FAK, Rac1, and lck) while disrupting epidermal growth factor receptor (EGFR)-α(6) integrin collaboration. Underlying these defects, CD151 ablation redistributed α(6)β(4) integrins subcellularly and severed molecular links between integrins and tetraspanin-enriched microdomains. In a prototypical basal-like mammary tumor line, CD151 ablation notably delayed tumor progression in ectopic and orthotopic xenograft models. These results (a) establish that CD151-α(6) integrin complexes play a functional role in basal-like mammary tumor progression; (b) emphasize that α(6) integrins function via CD151 linkage in the context of tetraspanin-enriched microdomains; and (c) point to potential relevance of CD151 as a high-priority therapeutic target, with relative selectivity (compared with laminin-binding integrins) for pathologic rather than normal physiology.